PECULIARITIES OF THE ORGANISM RESPONSE TO PHYSICAL LOAD IN SCHOOLCHILDREN OF THE HIGHEST GRADES WITH INSUFFICIENT BODY WEIGHT - Ponomarev, G.N.; Volkova, N.L.; Kvashnina, E.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to reveal the results of the study of the level of physical fitness of schoolchildren with insufficient body weight. Methods and structure of the study. The results of testing to assess the level of development of basic physical qualities are given, a comparative analysis is carried out with the results of testing schoolchildren with normal and overweight. It was found that with a relatively equal general level of physical fitness in schoolchildren with insufficient body weight, compared with schoolchildren with normal body weight, the former have a more pronounced disharmony in the development of physical qualities. A comparison of the reactions of the body to physical activity during physical education lessons in schoolchildren with insufficient and normal body weight is presented. The specific features of the impact of physical education lessons according to the standard school curriculum on the cardiovascular system of schoolchildren with insufficient body weight were revealed. Results and conclusions. Underweight students in general did not show statistically significant differences in the level of physical fitness compared to students with normal body weight. The mean score on all tests is 4, compared to 4.06 for normal weight students. Overweight students have an average score of 3.34 on all tests. Thus, it can be concluded that underweight does not affect the level of physical fitness to the same extent as overweight.